Encoding of Text Reuse in the Project Beta maṣāḥǝft - Daria Elagina (Journal of the Text Encoding Initiative)
The paper discusses the phenomenon of text reuse in the manuscript tradition of Ethiopia and Eritrea and, by examining examples of different forms of text reuse, presents the possibilities of its encoding in TEI XML within the frame of the project Beta maṣāḥǝft. Text reuse, which consists in the implicit or explicit repetition of text, is attested in a variety of forms, including quotations, allusions, paraphrases, and cross-linguistic text reuse. The documentation of this practice contributes to the study of different aspects of the manuscript tradition, for example, to the impact and relative dating of texts, and history of their transmission. The variety of text reuse forms allows for different approaches to their encoding which are presented in this paper to illustrate the possibilities of text reuse markup within the project’s schema. Additionally, the paper discusses the concept of narrative units and its difference to the concept of text reuse, as well as the markup of a type of text reuse which involves the reference to external entities.